AN ANALYSIS ON THE FACTORS INFLUENCING THE SECOND LANGUANGE ACQUISITION (STUDENTS’ ENGLISH LEARNING ACHIEVEMENT) OF THE USHULUDDIN, ADAB AND DA’WAH STUDENTS - Wardah Wardah (INSTITUT AGAMA ISLAM NEGERI PONTIANAK, 2018)
This research was conducted for factors (internal and external) which influences students’ second language acquisition (students’ learning achievement). This research has investigated the effect relation of the factors on students’ learning achievement and the factors which influence the students’ learning achievement and the factors that comes from the students that influencing the students’ second language acquisition (learning achievement).This research use quantitative research. This research conducted in Ushuludddin, Adab and Da’wah Faculty, especially for 5 majors. The sample of this research about 100 students. The data in this research were collected by documentation technique and questionnaire technique. In analyzing the data, the researcher using Multiple Regression Analysis (SPSS 17), T test, F test, and Coefficient Determination (R2). Motivation, personal practice, study habits, and input has significant effect to the students’ learning achievement. Attitude, social factors and interaction has no significant effect to the students’ learning achievement. (Penelitian ini dilakukan untuk mengetahui faktor-faktor (internal dan eksternal) yang mempengaruhi akuisisi bahasa kedua mahasiswa (prestasi belajar mahasiswa). Penelitian ini telah meneliti hubungan pengaruh antara faktor-faktor prestasi belajar mahasiswa dan faktor-faktor yang mempengaruhi prestasi belajar mahasiswa, serta faktor-faktor yang berasal dari mahasiswa yang mempengaruhi akuisisi bahasa tersebut. Penelitian ini menggunakan pendekatan kuantitatif. Penelitian ini dilakukan di Ushuludddin, Adab dan Fakultas Dakwah, khususnya pada 5 jurusan. Sampel penelitian ini sekitar 100 mahasiswa. Data dalam penelitian ini dikumpulkan dengan teknik dokumentasi dan teknik kuesioner. Dalam menganalisis data, peneliti menggunakan Analisis Regresi Berganda (SPSS 17), uji T, uji F, dan Koefisien Determinasi (R2). Motivasi, praktik pribadi, kebiasaan belajar, dan masukan memiliki pengaruh yang signifikan terhadap pencapaian belajar mahasiswa. Sikap, faktor sosial dan interaksi tidak berpengaruh signifikan terhadap prestasi belajar mahasiswa).